Ambrose W. Thompson papers - Thompson, Ambrose W.
Business and family correspondence, letterbooks, memoranda, reports, statistical tables, patent papers, stocks and bonds, printed matter, drawings, maps, and other papers relating chiefly to Thompson's business interests in canals, land speculation, railroads, and steamships. Records of the Chiriqui Improvement Company pertain to its efforts to establish a colony of freedmen from the District of Columbia in Chiriqui Province, Panama, as well as to develop the company's transportation and mining interests in Panama. Includes correspondence of Thompson's son, Ambrose Thompson, Jr., pertaining to his role in his father's enterprises. Correspondents include James Mitchell Ashley, Edward Fitzgerald Beale, Simon Cameron, John A. Dix, William Maxwell Evarts, Lucius Fairchild, Gustavus Vasa Fox, William Henry Hurlbert, Abraham Lincoln, Thomas Francis Meagher, Juan Pattison, Francis Harrison Pierpont, S.C. Pomeroy, David D. Porter, Fitz-John Porter, Samuel Shellabarger, Franz Sigel, Caleb B. Smith, Richard W. Thompson, John Palmer Usher, and Henry A. Wise.
Businessman. Born 1811. Died 1882.
Collection material in English, with Spanish, German, and French.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Ashley, James Mitchell, -- 1824-1896 -- Correspondence; Beale, Edward Fitzgerald, -- 1822-1893 -- Correspondence; Cameron, Simon, -- 1799-1889 -- Correspondence; Dix, John A. -- 1798-1879 -- Correspondence; Evarts, William Maxwell, -- 1818-1901 -- Correspondence; Fairchild, Lucius, -- 1831-1896 -- Correspondence; Fox, Gustavus Vasa, -- 1821-1883 -- Correspondence; Hurlbert, William Henry, -- 1827-1895 -- Correspondence; Lincoln, Abraham, -- 1809-1865 -- Correspondence; Meagher, Thomas Francis, -- 1823-1867 -- Correspondence; Pattison, Juan -- Correspondence; Pierpont, Francis Harrison, -- 1814-1899 -- Correspondence; Pomeroy, S. C. -- 1816-1891 -- Correspondence; Porter, David D. -- 1813-1891 -- Correspondence; Porter, Fitz-John, -- 1822-1901 -- Correspondence; Shellabarger, Samuel, -- 1888-1954 -- Correspondence; Sigel, Franz, -- 1824-1902 -- Correspondence; Smith, Caleb B. -- 1808-1864 -- Correspondence; Thompson, Ambrose, -- Jr. -- Correspondence; Thompson, Richard W. -- 1809-1900 -- Correspondence; Usher, John Palmer, -- 1816-1889 -- Correspondence; Wise, Henry A. -- 1806-1876 -- Correspondence; Thompson family -- Correspondence; Chiriqui Improvement Company; African Americans -- Colonization; African Americans -- Washington (D.C.); Canals; Freedmen -- Colonization; Land speculation; Mines and mineral resources -- Panama; Railroads; Steamboats; Transportation -- Panama; Chiriquí (Panama : Province); Panama -- Colonization; Panama -- History -- To 1903.; Businessmen